Organic electronic and photonic devices based on pentacene and modified oligo-p-phenylenevinylenes - Gorjanc, Timothy C (University of Ottawa (Canada), 2005)
This thesis is an account of the fabrication of organic field effect transistors using pentacene and two novel oligomers; bis-(4,4'-(biphenyl)ethenyl)phenyl and bis-(4,4'-(octylbiphenyl)ethenyl)phenyl. Organic light emitting diodes were also fabricated using bis-(4,4'-(biphenyl)ethenyl)phenyl and bis-(4,4'-(octylbiphenyl)ethenyl)phenyl in various configurations. A hole field effect mobility of 2.4 cm2-/Vs was observed in pentacene transistor. To our knowledge, this is one of the highest field effect mobilities obtained from a polycrystalline pentacene thin film. bis-(4,4'-(biphenyl)etlhenyl)phenyl displayed extremely poor film forming qualities and did not exhibit any significant field effect. A hole field effect mobility of 0.31 cm2/Vs was achieved using bis-(4,4'-(octylbiphenyl)ethenyl)phenyl. In order to fabricate high quality organic field effect transistors, a self assembled monolayer is usually applied to the gate dielectric prior to the deposition of the organic semiconductor. Three monolayers have been studied: hexamethyldisilazane,n-octyltrichlorosilane, and n-octadecyltrichlorosilane. Through a systematic process, monolayer deposition recipes were developed which resulted in the formation of ultra-smooth surfaces with contact angles of 75-80° for hexamethyldisilazane and 105-110° for the two trichlorosilane derivatives. The formation of ultra-smooth monolayers is critical to fabricating an organic transistor with superior operating characteristics. The oligomers were characterized using cyclic voltammetry to determine the energy levels and differential scanning calorimetry to study their thermal behaviour. Optical absorption and fluorescence spectroscopy was performed to determine the onset of absorption and the main emission wavelengths. The electronic spectra of the oligomers were modeled using semi-empirical quantum mechanical calculations (PM3 and Zindo). Polycrystalline thin films were grown in high vacuum using a Knudsen cell. The substrate temperature was held between room temperature and 225°C. The resulting films were characterized by powder x-ray diffraction and atomic for microscopy. Both of these techniques indicated that the thin films formed a lamellar structure parallel to the substrate surface with the lamella thickness corresponding to the length of the molecule, between 42 and 44 A. The different monolayers did not seem to effect the thickness of the lamella but did increase the size of the grains. Both oligomers were used in single and multi-layer organic light emitting diodes. The single layer organic light emitting diodes displayed faint electroluminescence while the multi-layer devices displayed more intense electroluminescence. The electroluminescence and fluorescence spectra are identical, indicating that recombination occurs solely within the oligomer layer. In the multi-layer organic light emitting diodes, different hole transporting materials such as were used in conjunction with the oligomers, which were employed as the emitter. The devices that generated the most intense electroluminescence were the N,N'-diphenyl-N,N'-bis(3-methylphenyl benzadine)/bis-(4,4'-(octylbiphenyl)ethenyl)phenyl device had a luminance of 174 cd/m2 and the N,N'-diphenyl-N,N'-bis(3-methylphenyl benzadine)/bis(4,4'-(biphenyl)ethenyl)phenyl device was brighter with a luminance of 580 cd/m2.
Keywords: Physics, Condensed Matter.